Nebulized glycyrrhizin/enoxolone drug modulates IL-17A in COVID-19 patients: a randomized clinical trial - Zendejas-Hernandez, Ulises; Alcántara-Martínez, Nemi; Vivar, Diana Tovar; Valenzuela, Fermín; Sosa Espinoza, Alejandro; Cervera Ceballos, Eduardo Emir (Frontiers in Immunology, 2024)
Glycyrrhizin (GA) and its derivative Enoxolone (18β), isolated from the Glycyrrhiza glabra plant, are two potential molecules for treating viral diseases. Both demonstrate to regulate immune system with antiviral and anti-inflammatory activities, with the latter mainly due to modulation of inflammatory cytokines. The aim of this clinical trial was to evaluate the safety and efficacy of a nebulized GA/18β drug for treating patients. An open label, randomized, placebocontrolled clinical trial was conducted in Mexico City from January-August 2022 (Registration No. PROTAP-CLI-00). Clinical and biochemical parameters were recorded. Blood samples from patients were regularly collected to evaluate interleukins